Effect of a 60-day weight reduction intervention prior to IVF/ICSI on perinatal outcomes in overweight or obese infertile women - Yang, Chen; Yang, Shuheng; Zheng, Wei; Zu, Ruowen; Ran, Shiyu; Wu, Huan; Ren, Bingnan; Lv, Ning; Kuang, Yihui; Li, Mengna; Du, Jiangbo; Guan, Yichun (Frontiers in Endocrinology, 2022)
Purpose The aim of this study was to determine whether a 60-day weight reduction intervention prior to in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) and a higher weight loss ratio effectively improved perinatal outcomes for infertile overweight or obese women. Methods This was a retrospective cohort study conducted at a university-affiliated fertility center. Two thousand three hundred and eighty-one overweight or obese infertile women who underwent or did not undergo a 60-day weight reduction intervention prior to IVF/ICSI between February 27, 2017 and November 11, 2020 were included in this study. All of these women achieved clinical pregnancy and delivered a single child after assisted reproductive technology (ART). Primary outcomes included neonatal birth weight and the incidence of pregnancy complications, premature delivery, and low birth weight. Results The body mass index (BMI), blood glucose concentration, serum insulin level, and homeostasis model assessment of insulin resistance (HOMA-IR) of the intervention group decreased significantly after the weight reduction intervention. Neonatal birth weight was significantly higher in the intervention group (3519.6 g ±484.8 g) than the control group (3406.8 g ± 554.2 g; P < 0.001). There was no significant difference in the incidence of pregnancy complications between the two groups. Linear regression analysis found that the weight reduction intervention prior to IVF/ICSI and lower HOMA-IR at ovulation induction were associated with increased birth weight. As the weight loss ratio increased, the incidence of hypertensive disorders of pregnancy, premature membrane rupture, premature delivery, stillbirth, and low birth weight showed a downward trend. Conclusion(s) A 60-day weight reduction intervention prior to IVF/ICSI may increase neonatal birth weight, reduce maternal blood glucose concentration, and improve maternal insulin resistance in infertile overweight or obese women. This results require to be further verified by prospective randomized controlled trials with a larger sample size.